A Brønsted Acidic Ionic Liquid as an Efficient and Selective Catalyst System for Bioderived High Molecular Weight Poly(ethylene 2, 5‐furandicarboxylate). Issue 22 (17th October 2019) - Qu, Xiao‐ling; Jiang, Min; Wang, Bing; Deng, Jin; Wang, Rui; Zhang, Qiang; Zhou, Guang‐yuan; Tang, Jun
Abstract: Green synthesis of bioderived high‐molecular‐weight poly(ethylene 2, 5‐furandicarboxylate) (PEF) over metal‐free catalysts is a significant challenge. This study focuses on PEF prepared from ethylene glycol and 2, 5‐furandicarboxylic acid (FDCA) through a direct esterification method with ecofriendly metal‐free ionic liquids (ILs) as catalysts. The catalytic activities of a series of imidazolium cations in the presence of various anions are systematically investigated and found to be mainly governed by the anions. Among the ILs studied, 1‐ethyl‐3‐methylimidazolium tetrafluoroborate ([C2 MIM]BF4 ) is identified as the best catalyst, showing excellent catalytic activity, selectivity, and stability, even at low catalyst loadings (0.1 mol % w.r.t. FDCA). Optimization of the polymerization parameters enables [C2 MIM]BF4 ‐catalyzed production of PEF with a high number‐average molecular weight ( M n =5.25×10 4  g mol −1 ). The relationship between Brønsted acidity and catalytic activity is also investigated and the results show that the trend in catalytic activity is in good agreement with that in Brønsted acidity, as determined by the Hammett method. Additionally, on the basis of experimental results and density functional theory calculations, an electrophilic activation mechanism induced by hydrogen bonds is proposed. This strategy of adjustable acidity and anion structure in ILs provides an opportunity to develop other ILs for bio‐based polyesters through green synthesis pathways. Abstract : Low loading : With a small catalyst loading of metal‐free and selective ionic liquids (0.1 % based on 2, 5‐furandicarboxylic acid), bioderived poly(ethylene 2, 5‐furandicarboxylate) is efficiently prepared with high molecular weight by the electrophilic activation induced by hydrogen bonds, which are formed between the ionic liquid [C2 MIM] + and the carbonyl oxygen.